Resist nanokirigami for multipurpose patterning. Issue 11 (31st December 2021) - Liu, Qing; Chen, Yiqin; Feng, Zhanyong; Shu, Zhiwen; Duan, Huigao
Abstract: Resist-based patterning solutions play essential roles in modern micro- and nanoscale science and technology. The commonly used 'resist' patterning strategy depends on selective-area scission or cross-linking of resist molecules under the action of an energy beam. In this work, we propose and demonstrate a different resist-patterning strategy, termed 'resist nanokirigami', in which the resist structures are defined by their outlines and revealed by selective mechanical peeling of the unwanted resist film. Unlike conventional resist-based patterning processes, the final resist-nanokirigami structures do not undergo exposure and the exposure area is dramatically reduced. With these two advantages, a variety of functional structures that are difficult or impossible to fabricate by conventional processes, such as inverse nanostructures and their oligomers, multi-scale electrodes and freestanding plasmonic nanogaps, can be easily achieved with much higher efficiency. Thus, with its unique and complementary capabilities, the resist-nanokirigami process provides a new patterning solution that expands the family of lithography techniques and will play a significant role in fabricating multi-scale functional structures. Abstract : This paper demonstrates a novel lithography strategy based on resist nanokirigami, which can greatly improve the processing efficiency and reduce the proximity effect of electron beam lithography to define multiscale resist structures for multipurpose applications.